Determination of trace heavy metals (Copper and Lead) in different tissues of Siganus rivulatus (Seganidae) in the southern part of Syrian Coast and its suitability for human consumption - سعد, أديب; حمود, فينا; سليمان , يانا (Latakia University Journal -Biological Sciences Series, 2022)
This study deals with the determination of two heavy metals Copper (Cu) and Lead (Pb) in the muscles and liver of economic fish species Siganus rivulatus (Seganidae),which were collected from three sites in the Syrian Coast vary in the level of contamination, during August 2019 to May 2020. The aim of the study is to assess the concentraion levels of these metals in the fish tissus and their transition in food chains and their arrival to human body. The results showed that the muscles had the lower metal concentrations of copper and Lead with an average of (0.636 -0.0185 µg/g wet weight) respectively, compared with the liver with an average of (40.48-0.179 µg/g wet weight) respectively. Changes in the concentrations of metals (copper and lead) were observed due to the sampling areas. None of the values in the muscles exceeded the permissible extents, hence would not couse any hazard to health consumers.